Effect of tiger-nut (Cyperus esculentus) milk co-product on the surface and diffusional properties of a wheat-based matrix. (1st June 2017) - Verdú, Samuel; Barat, José M.; Alava, Cecibel; Grau, Raúl
Highlights: Industrial tiger-nut milk by-product has high insoluble fibre content. Two different flours from by-product tissues components were tested. Wheat-based matrix were prepared at different substitution levels: 5%, 10% and 20%. Matrices surface tension, wettability and diffusion of water and oil were tested. Reduction on surface tension, wettability and diffusion of solvents were observed. Abstract: The food processing industry generates huge volumes of waste and co-products which still contain valuable compounds. Tiger-nut milk production generates large amounts of a co-product with a high insoluble fibre content, which is interesting as a bioactive component from a nutritional viewpoint. This co-product is formed by two different tissues in composition, particle size and colour terms, so two different flours were obtained from them. Both flours were included in a wheat-based matrix at different substitution levels: 5%, 10% and 20% (d.b). The surface tension of matrices, and the wettability and diffusion of water and oil, were studied. The results showed the matrix's reduced capacity to interact with solvents, principally from the 10% substitution level, with diminished surface tension, and a longer time was needed for both water and oil to wet and diffuse.